Unveiling the structuring effects of eutrophication on macrobenthic biological traits in Hangzhou Bay and adjacent waters - Zhou, Weiwei; Wang, Xiaobo; Han, Qingxi (Frontiers in Marine Science, 2024)
The ecological effects of eutrophication on estuaries and coastal ecosystems are significant w orldwide. Based on data collected in 2019 from the Hangzhou Bay and adjacent waters, this study inves tigated the distribution patterns of macrobenthic assemblages along a eutrophication gradient and revea led the response patterns of their biological traits to eutrophication stress. The results showed that eutro phication had a significant structuring effect on the spatial distribution of macrobenthic community stru cture. As the level of eutrophication increased, the community abundance and number of macrobenthic biological traits decreased. The composition of macrobenthic community biological traits changed in r esponse to eutrophication. In areas with high levels of eutrophication, larger body sizes became more d ominant, reflecting a shift in dominant traits similar to the eutrophication gradient. Furthermore, the pre dominant species in this region were burrowers and tube dwellers, which preferred muddy sand and san dy mud substrates. The AMBI ecological group accurately reflects the degree of eutrophication disturba nce, with tolerant species and second-order opportunistic species being common in eutrophic areas.